Impact of tourism for regional development: an alternative socio-economic model for Cambodia. (2016) - Homlong, Nathalie; Springler, Elisabeth
Numerous economic discourses in less developed economies have shown that standard economic approaches are not applicable. Conversely, alternative economic models aim to integrate factors, which are neglected in standard economic approaches: space, time and the specific structural and institutional settings of regions and nations. Applying alternative approaches, this paper aims to critically reflect on the effects of the promotion of the tourism sector in Cambodia on social and economic development. For this purpose Siem Reap, the province where the temples of Angkor Wat are located, is selected as case study. Siem Reap is one of the top tourism destinations in Cambodia. Nonetheless, regional GDP is among the lowest among Cambodia's provinces. Tourism development is promoted as a way towards development for the region. While tourism has indeed been creating jobs in Siem Reap, the question arises whether the local population has been benefiting from tourism development.